Native Sinus Hemodynamics and Thrombosis in Transcatheter Heart Valve: Effect of Implant Depth and Coronary Flow - Hyun Jung Koo; Jihun Kang; Do‐Yoon Kang; Jung‐Min Ahn; Duk‐Woo Park; Seung‐Jung Park; Joon‐Won Kang; Hojin Ha; Dong Hyun Yang (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background This study aimed to investigate the hemodynamic and anatomic factors associated with sinus thrombosis following transcatheter aortic valve replacement (TAVR), integrating in vivo patient data analysis and in vitro experiments. Methods and Results Postprocedural, 4‐dimensional, multiphase computed tomography data from 211 patients enrolled in the ADAPT‐TAVR (Anticoagulation Versus Dual Antiplatelet Therapy for Prevention of Leaflet Thrombosis and Cerebral Embolization After Transcatheter Aortic Valve Replacement) study were analyzed. The prevalence of native sinus thrombosis was examined in relation to valve type, implant depth, and anatomic features. In vitro experiments used particle image velocimetry to observe changes in sinus flow based on the transcatheter heart valves (23‐mm SAPIEN3, Edwards Lifesciences; and 29‐mm CoreValve, Medtronic) height and coronary artery flow. Native sinus thrombosis was more common in self‐expanding valves (39.1% versus 14.9%, P=0.004). In per‐cusp analysis of in vivo patient data, adjusted transcatheter heart valve implant depth (odds ratio, 1.2 [95% CI, 1.1–1.3]; P<0.001), noncoronary sinus of Valsalva (odds ratio, 4.0 [95% CI, 2.0–7.8]; P<0.001), sinus inflow diameter (odds ratio, 0.8 [95% CI, 0.6–0.9]; P=0.008), and implanted valve size (odds ratio, 0.8 [95% CI, 0.7–1.0]; P=0.025) were significant factors associated with native sinus thrombosis. In the in vitro experiments, CoreValve showed noticeable flow stasis compared with SAPIEN3. High‐positioned SAPIEN3 was linked to reduced velocity within the native sinus of Valsalva. Coronary artery flow led to higher sinus velocity and improved particle washout, reducing sinus thrombosis risk. Conclusions This study provides insights into the relationship between transcatheter heart valve deployment and native sinus thrombosis, emphasizing the role of anatomic factors in relation to the risk of sinus thrombosis.